Case Study: Using a Shared International Database to Document Veterinary Consumption of Antibiotics in Pakistan - Mashkoor Mohsin; Umar Farooq; Maria Hartmann; Sandra Brogden; Lothar Kreienbrock; Julia Stoffregen (Antibiotics, 2023)
In this paper, we present a case study of Pakistan documenting the use of antimicrobial drugs in poultry flocks in the VetCAb-ID database. Unlike other databases, this system allows international users to upload their data directly. Based on expert interviews and a review of the latest publications on the topic, we provide an alternative approach to harmonizing data collection among countries. This paper will provide impetus to formulate joint requirement documentation for an AMU database on a global level that international users can adapt for their own purposes and projects.